Stark‐Localization‐Limited Franz–Keldysh Effect in InAlAs Digital Alloys. Issue 9 (12th June 2019) - Yuan, Yuan; Zheng, Jiyuan; Sun, Keye; Jones, Andrew H.; Rockwell, Ann K.; March, Stephen D.; Shen, Yang; Bank, Seth R.; Campbell, Joe C.
Abstract : The optical absorption characteristics of the InAlAs digital alloy semiconductor are investigated. The external quantum efficiency of the InAlAs digital alloy is compared with that of the In0.52 Al0.48 As random alloy. Unlike the random alloy, the digital alloy exhibits electric‐field‐induced Stark localization, which increases the optical absorption and suppresses the Franz–Keldysh red shift of the optical absorption edge. Abstract : Studies of the absorption edge of a semiconductor provide insight into the absorption characteristics and the band structure. In this paper, the absorption properties of a digital alloy material have been studied and compared with those of a random alloy. It was found that Stark localization makes the absorption edge more abrupt than the Franz–Keldysh effect observed in random alloys.